Digital Technologies in Health Care: A Comprehensive Review of Current Status and Future Perspectives - Ghafar, Zanyar (International Journal of Applied and Scientific Research, 2024)
The review paper focuses on the most important digital technologies that are used in health care, as well as the difficulties, advantages, and prospective prospects for the future that are linked with the inclusion of digital tools into clinical learning. Within the context of this rapidly evolving digital age, it is of the highest significance for students, medical educators, and training organizations to keep their understanding of the breadth, promise, difficulties, and limitations of digital technologies up to date. Digital health studies aim to realize the promise of digital technologies and understand their feasibility and effects. Through a critical examination of the most famous interdisciplinary digital health publications, this study argues that the digital health field has not really engaged with its main topic, technology. The intricacies of healthcare environments, including different technologies, existing procedures, and people, are ignored in research on digital technologies. The study findings show that health literature focuses on digital technology processing and its effects on digital health research approaches that emphasize technology and context. It claims that digital health's full potential requires multidisciplinary research on healthcare systems, informational demands, and digital technology.